2023
DOI: 10.4103/jcrt.jcrt_1471_22
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 expression in rare and aggressive thyroid cancers: A preliminary investigation for a role of immunotherapy

Abstract: Background and Aim: Programmed cell death ligand-1 (PD-L1) immunoexpression status determines the response to immunotherapy in many cancers. Limited data exist on PD-L1 status in aggressive thyroid tumors. We investigated PD-L1 expression across thyroid cancers and correlated it with their molecular profile. Materials and Methods: Sixty-five cases of differentiated thyroid carcinoma, poorly differentiated thyroid carcinoma (PDTC), and anaplastic thyroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Blocking this protein may increase the action of BRAF-V600E gene inhibitors, thus preventing the progression of the mutated malignancy[ 51 ]. PD-L1 expression was found to be positive in a high proportion in papillary 87% but with weaker and patchy expression, and in anaplastic thyroid carcinoma 73%, indicating that the latter can exhibit a better response to immunotherapy[ 59 ].…”
Section: Diagnosismentioning
confidence: 99%
“…Blocking this protein may increase the action of BRAF-V600E gene inhibitors, thus preventing the progression of the mutated malignancy[ 51 ]. PD-L1 expression was found to be positive in a high proportion in papillary 87% but with weaker and patchy expression, and in anaplastic thyroid carcinoma 73%, indicating that the latter can exhibit a better response to immunotherapy[ 59 ].…”
Section: Diagnosismentioning
confidence: 99%
“…In DTC, the positivity of PD-L1 varied among studies. Although two studies focusing on PTC reported low PD-L1 positivity rates, ranging from 6.1 to 10.1% [ 53 , 84 ], other studies reported higher PD-L1 positivity rates, ranging from 0.3 to 87% [ 47 , 85 , 86 ]. It should be noted that the expression of PD-L1 is significantly higher in aggressive PTC than in non-aggressive PTC [ 85 ].…”
Section: The Immunological Targets and Immunization In Tcmentioning
confidence: 99%
“…PD-L1 expression is relatively low, with positivity rates ranging from 12.5 to 14.4% in MTC [ 88 , 89 ]. In ATC, the expression of PD-L1 is relatively high, ranging from 60 to 81.3% [ 53 , 86 , 90 , 91 ]. A direct comparison between histological types has shown that higher expression of PD-L1 is observed in ATC than in DTC [ 84 , 86 ].…”
Section: The Immunological Targets and Immunization In Tcmentioning
confidence: 99%
See 2 more Smart Citations